The LGBT activism of Jason Jones. Issue 2 (22nd December 2022) - Jones, Jason; Wahab, Amar
Abstract : Scholar Amar Wahab, co-editor of the Journal of Indentureship and Its Legacies, interviews LGBTQ+ human rights defender Jason Jones about his advocacy spanning four decades in Trinidad and Tobago and the UK. Jones shares his experiences about the intersections of homophobia and racism to highlight the complexities around LGBTQ+ human rights. He discusses his successful landmark legal challenges against state-sponsored legal homophobia in both spaces.